2009
DOI: 10.1038/cgt.2009.77
|View full text |Cite
|
Sign up to set email alerts
|

Bovine herpesvirus type 1 as a novel oncolytic virus

Abstract: Oncolytic virotherapy is a promising avenue of cancer gene therapy. Current vectors include human viruses that have been engineered to replicate in tumor cells or nonhuman viruses that are naturally oncotropic and preferentially replicate in tumor cells harboring defects in innate immune pathways such as the type 1 interferon (IFN) pathway. Bovine herpesvirus type 1 (BHV-1) is a species-specific herpesvirus closely related to the human herpes simplex virus type 1 (HSV-1). Although BHV-1 does not efficiently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Data from our group indicate that BHV-1 oncolysis does not correlate with defects in type I IFN signaling (22). Furthermore, BHV-1 is able to distinguish between normal and immortalized cell types (22), suggesting that immortalization and cellular changes occurring during this process may confer sensitivity to BHV-1. However, mutations in TP53 and retinoblastoma (RB1) protein, which are commonly deregulated during immortalization, do not correlate with permissivity to BHV-1 (Fig.…”
Section: Knockdown Of Mutant Kras Decreases Bhv-1 Titersmentioning
confidence: 87%
See 3 more Smart Citations
“…Data from our group indicate that BHV-1 oncolysis does not correlate with defects in type I IFN signaling (22). Furthermore, BHV-1 is able to distinguish between normal and immortalized cell types (22), suggesting that immortalization and cellular changes occurring during this process may confer sensitivity to BHV-1. However, mutations in TP53 and retinoblastoma (RB1) protein, which are commonly deregulated during immortalization, do not correlate with permissivity to BHV-1 (Fig.…”
Section: Knockdown Of Mutant Kras Decreases Bhv-1 Titersmentioning
confidence: 87%
“…To fully appreciate the oncolytic capacity of BHV-1, particularly in light of its unique properties (22,23), we screened the NCI panel of 59 established human tumor cell lines, comparing BHV-1 to our prototypic HSV-1 vector KM100. The capacities of BHV-1 and KM100 to initiate replication in and decrease the viability of the NCI panel were assessed.…”
Section: Bhv-1 Replicates and Reduces Cytotoxicity In A Wide Range Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, cattle farmers whom are routinely exposed to the virus do not seroconvert. Rodrigues et al (2010) showed that human transformed and phenotypically normal immortalized cell types are permissive to BHV-1, while normal primary cell types are relatively resistant to BHV-1 infection (Figure 2). BHV-1 induces cytopathic effects (CPE) and decreases cellular metabolism in immortalized and transformed cells from the lung, mammary, bone and prostate origins with varying efficiency.…”
Section: Bovine Herpesvirus Typementioning
confidence: 99%